Riverine macroplastic monitoring in Myanmar: sources and pollution dynamics in the Bago River - Rachel Hurley; Vilde Kloster Snekkevik; May Thazin Phoo; Kyaw Min San; Hans Nicolai Adam (Microplastics and Nanoplastics)
Abstract Global plastic pollution has been highlighted as an important environmental issue that requires urgent attention. Macroplastics, plastic items >2.5 cm, contribute the majority to global plastic pollution by mass and are the easiest to manage or remove, whilst also representing the dominant source of smaller plastic particles to the environment, such as microplastics. The Association of Southeast Asian Nations (ASEAN) has called for Member States to develop and implement national action plans for reducing plastic pollution. Yet, data to meaningfully underpin and effectively tailor such a plan for Myanmar are currently completely lacking. In this study, we investigate spatiotemporal variabilities in plastic pollution in the Bago River, examining the magnitude and diversity of macroplastic and how this is affected by the Bago City urban area and seasonal dynamics. Macroplastic flows were counted and characterised using a visual observation approach at upstream, within the city, and downstream sites from April to August 2023 – representing the first study of its kind for Myanmar. Bago City was confirmed to act as a source of plastic pollution, demonstrated through an increase in both pollution levels and diversity. Dominant categories of litter included food packaging, expanded polystyrene fragments, plastic bags, plastic bottles, and sachets. Macroplastic flows were highest during the dry season and reverse flow events during tidal floods were observed to cause significant recirculation of plastic litter in the catchment. These data reveal important sources and release pathways for macroplastic that can help to target relevant emissions in mitigation actions and policies and facilitate an effective reduction in plastic pollution in Myanmar.